Unhappy Offspring? Concubines and Their Sons in Early Abbasid Society. (20th January 2017) - Gordon, Matthew
Abstract : Contemporary and later Arabic texts provide much evidence that wayward conduct by elite young adult males was a source of considerable stress in early Abbasid cities. This brief essay turns on a question: to what extent is such conduct to be attributed to concubinage? I treat two sample texts, each describing untoward activity on the part of well-placed adult sons and its impact on the Abbasid body politic. Neither text, however, speaks to concubinage. What follows, then, is an argument from circumstantial evidence. Concubinage seems a most likely source, and so can reasonably be connected to the broader patterns of social disjunction of the first Abbasid period (roughly the mid-8th to mid-10th centuries).